The relevance of recognizing clinical and morphologic features of pityriasis lichenoides: clinicopathological study of 29 cases - Jandrei Rogério Markus; Vânia Oliveira Carvalho; Monica Nunes Lima; Kerstin Taniguchi Abagge; Alexandre Nascimento; Betina Werner (Mattioli1885, 2013)
Background: Pityriasis lichenoides (PL) is a lymphoproliferative disease of unknown origin; its diagnosis is based on clinical characteristics and confirmed by histology. Objectives: To describe clinical and histological features of PL in 29 pediatric patients. Materials and Methods: Retrospective descriptive study of children (patients less than 15 years old) diagnosed with PL between 1986 and 2010 at a Reference Service in Pediatric Dermatology from South Brazil. Results: Twenty-nine PL cases were found by chart review in 24 years. Mean age of diagnosis was 8 years (22 to 178 months) and a mean time of diagnosis was 13.8 months (1 to 120 months). Twenty cases (69%) were male. Seasonal correlation was found with colder months in 62% of cases (p< 0.01). Clinical diagnosis was pityriasis lichenoides chronica (PLC) in 25 cases, and pityriasis lichenoides et varioliformis acuta (PLEVA) in four. Itching was the main reported symptom occurring in 13 (45%). Fourteen cases had been histologically evaluated. In six, microscopic findings were consistent with PLC, in four consistent with PLEVA, and four biopsies exhibited mixed characteristics of both forms. Concordance between clinical and histological diagnosis was seen in most cases. Conclusion: PL occurs in children and young adults, more commonly in males, and during cold months. PLC was the more frequent clinicohistologic form, and necrotic lesions characterized PLEVA. Associating clinical and histological findings is important for differentiating between PLC and PLEVA diagnosis.